Preserving Local Cultural Values in Forming the Character of Patriotism in Elementary School Students in Wonogiri Regency - Retno Handayani; Sabar Narimo; Djalal Fuadi; Minsih Minsih; Choiriyah Widyasari (Journal of Innovation in Educational and Cultural Research, 2023)
Local cultural diversity must be preserved and developed from generation to generation while maintaining the values contained therein. Media inheriting local cultural diversity can be done through education. Education in local content is intended so that students have solid insight into their environment and attitudes and behaviors that are willing to preserve and develop natural resources, social quality, and culture that support national and local development. The purpose of this study was to examine the preservation of local cultural values in Wonogiri Regency as an effort to build the character of the homeland. The method in this study uses a qualitative approach with an ethnographic design. The ethnographic model used is descriptive ethnography because it describes local cultural values in Wonogiri Regency. The place of research was conducted in one of the elementary schools in Wonogiri Regency. Data were collected from interviews, documentation, and observations. The results of the study show that the introduction of local culture in elementary schools can be done by introducing dance, types of musical instruments, folk songs, and regional languages, and integrating local products that must be guarded and preserved. Preservation of local cultural values is an effort made by schools as educational institutions to make the values of art, language, and folk songs as the basis for efforts to form the characteristics of love for the homeland. The challenges in the process of preserving local culture are the influence of globalization and the local government's lack of understanding of local culture in Wonogiri Regency.